Homozygous R396H mutation of the RAG1 gene in a Saudi infant with Omenn's syndrome: a case report - Al Balwi, Mohammed; Al Ajaji, Sulaiman; Al Abdulkareem, Ibrahim; Hajeer, Ali (Cases journal, 2009)
The V(D)J rearrangement of B and T cell lymphocytes during the recombination process, which is essential for the development of normal immune system function, depends critically on the presence of the recombination activating enzymes, RAG1 and RAG2. Mutations in RAG1 or RAG2 can lead to a spectrum of disorders, ranging from typical B-T-severe combined immunodeficiency to Omenn's syndrome. A two-month-old Saudi baby girl presented with fever, respiratory distress due to bronchiolitis, exfoliative erythroderma and a family history of childhood death within the first few months of life in two of her sisters who had had a similar clinical presentation to her own. Immunological work-up revealed an absence of circulating B lymphocytes, whereas various numbers of activated T lymphocytes were present in the peripheral blood and in the skin. In this case, mutation analysis of the recombination activating genes RAG1 or RAG2 revealed a homozygous missense (c.1299G>A) mutation in the RAG1 gene. This is the first report in the literature linking a homozygous R396H mutation in the RAG1 gene with presentation of Omenn's syndrome.